Planificación estratégica para el Gobierno Autónomo Descentralizado de la Parroquia Urdaneta-Cantón Saraguro periodo 2019-2023 - Maldonado Nagua, Johanna Daniela (2018)
His research entitled “Strategic Planning for the Autonomous Decentralized Government of the Parish Urdaneta-Cantón Saraguro period 2019-2023” was elaborated with the goal of to plaster the needs of the Parochial Government, as a information, decision and control tool to improve administrative management and of this way, achieve the objectives and institutional goals. The development of present work is aligned to a theoretical, explanatory and practical methodology which served to demonstrate what it is to establish a strategic planning proposal and how to optimize the performance of the Parochial Government of Urdaneta. The results reflected in this present work the fulfillment of yhe objectives was done starting of a situational diagnosis both internally and externally; allowing to know the current situation of the Parish GAD, its capabilities, limitations and the financial situation of it with the purpose of establishing the direction through the elaboration of different matrices which contributed for the formulation of strategies and plans of action that will help to optimize the time and resources to accomplish the programmed goals and activities, improving administrative management. Based on the study conducted at the Parish GAD, it is concluded that the entity has not designed a strategic planning that promotes institutional progress and therefore achieve a better performance in their activities, in addition, it has been possible to show the dissatisfaction of the inhabitants due to the lack of priority works since they are not adequately addressed because the few works executed are for the benefit of a few. Finally, recommend that the GAD Parroquial officials should receive continuous training that allows them to enrich the knowledge to improve their management and offer a quality service to the inhabitants of the parish.